Inguinal hernia with ovary as content- laparoscopic repair in a Mayer–Rokitansky–Küster–Hauser syndrome patient: case report - Khan, Washim F.; Rathore, Yashwant S.; Pol, Manjunath M.; Singh, Gurpremjit (International Surgery Journal, 2019)
Inguinal hernia is a common surgical disease. Ovary and fallopian tube are not frequently found as content of the hernia. A 18 year old female, diagnosed case of Mayer–Rokitansky–Küster–Hauser (MRKH) syndrome, presented with left sided reducible inguinal hernia for six months. Ultrasonography revealed absence of intra-abdominal left ovary and presence of ovary in the sac. She was planned for laparoscopic repair and total extra-peritoneal repair (TEP) was done. Ovary and adnexa may be content in groin hernia in females. Association of syndromes especially MRKH syndrome should be kept in mind in this group of patients. Laparoscopic total extra-peritoneal repair may be successfully attempted in this group of patients.